Difference between revisions of "022 Exam 2 Sample B, Problem 7"
Jump to navigation
Jump to search
Line 22: | Line 22: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Step 1: | + | !(a) Step 1: |
|- | |- | ||
− | |(a) Use a ''u''-substitution with <math style="vertical-align: -8%">u = 3x^2 + 1.</math> This means <math style="vertical-align: 0%">du = 6x\,dx</math>, or <math style="vertical-align: -20%">dx=du/6</math>. | + | |(a) Use a ''u''-substitution with <math style="vertical-align: -8%">u = 3x^2 + 1.</math> This means <math style="vertical-align: 0%">du = 6x\,dx</math>, or <math style="vertical-align: -20%">dx=du/6</math>. Substituting, we have |
− | ::<math>\int x e^{3x^2+1}\,dx = \frac{1}{6} \int e^ | + | ::<math>\int x e^{3x^2+1}\,dx \,=\, \int xe^{u}\cdot\frac{du}{6}\,=\,\frac{1}{6}\int e^u\,du\,=\,\frac{1}{6}u. </math> |
− | |||
− | |||
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Step 2: | + | !(a) Step 2: |
|- | |- | ||
− | | | + | |Now, we need to substitute back into our original variables using our original substitution <math style="vertical-align: -5%">u = 3x^2 + 1</math> |
− | |||
|- | |- | ||
− | | | + | | to find <math style="vertical-align: -60%">\frac{1}{6}e^u = \frac{e^{3x^2 + 1}}{6}.</math> |
− | <math>\ | ||
− | |||
− | |||
− | |||
− | |||
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Step 3: | + | !(a) Step 3: |
|- | |- | ||
− | | | + | |Since this integral is an indefinite integral, we have to remember to add a constant  <math style="vertical-align: 0%">C</math> at the end. |
− | |||
− | |||
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! | + | !(b): |
+ | |- | ||
+ | |Unlike part (a), this requires no substitution. We can integrate term-by-term to find | ||
+ | |- | ||
+ | | | ||
+ | ::<math>\int_2^5 4x - 5 \, dx = 2x^2 - 5x \Bigr|_{x\,=\,2}^5.</math> | ||
|- | |- | ||
− | | | + | |Then, we evaluate: |
+ | |- | ||
+ | | | ||
+ | ::<math>\begin{array}{rcl}2x^2 - 5x \Bigr|_{x\,=\,2}^5 & = & 2(5^2) - 5(5) -(2(2)^2 - 5(2))\\ | ||
+ | & = & 50 - 25 -(8 - 10)\\ | ||
+ | & = & 25 +2\\ | ||
+ | & = & 27. | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 61: | Line 63: | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |(a) | + | |'''(a)''' |
− | ::<math>\frac{e^{3x^2 + 1}}{6} + C.</math> | + | ::<math>\int xe^{3x^2+1}\,dx\,=\,\frac{e^{3x^2 + 1}}{6} + C.</math> |
+ | |- | ||
+ | |'''(b)''' | ||
|- | |- | ||
− | | | + | | |
+ | ::<math>\int_2^54x - 5\,dx\,=\,27.</math> | ||
|} | |} | ||
[[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']] | [[022_Exam_2_Sample_B|'''<u>Return to Sample Exam</u>''']] |
Revision as of 10:02, 17 May 2015
Find the antiderivatives:
- (a)
- (b)
Foundations: |
---|
This problem requires Integration by substitution (u - sub): If is a differentiable functions whose range is in the domain of , then |
|
We also need our power rule for integration: |
|
Solution:
(a) Step 1: |
---|
(a) Use a u-substitution with This means , or . Substituting, we have
|
(a) Step 2: |
---|
Now, we need to substitute back into our original variables using our original substitution |
to find |
(a) Step 3: |
---|
Since this integral is an indefinite integral, we have to remember to add a constant at the end. |
(b): |
---|
Unlike part (a), this requires no substitution. We can integrate term-by-term to find |
|
Then, we evaluate: |
|
Final Answer: |
---|
(a)
|
(b) |
|